Improving Students' Basic Arabic Writing Skills (Imla Manzur) Through The Card Sort Method - Salma Sabila Yusuf; Maman Abdurrahman; Shofa Musthofa Khalid (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2023)
This research is quasi-experimental research conducted on class VIII students of SMP Mathlaul Anwar Margahayu, whose sample consists of two classes: experimental and control. This study aimed to determine the results of improving students' basic Arabic writing skills after learning imla manzur in collaboration with the card sort method. Of the 56 samples taken randomly and classified into two classes with different treatments, it was found that there was a difference between the results of the writing ability of the experimental class and the results of the control class' writing ability which was indicated by the results of the hypothesis testing of 0.000. The value of 0.000 <0.05 resulted in Ho being rejected and Ha is accepted, or it can be concluded that there was a significant influence on the learning outcomes of the imla manzur class applying the card sort method.